Optimized Syntheses of Optically Pure P-Alkene Ligands: Crystal Structures of a Pair of P-Stereogenic Diastereomers - Herrera, Alberto; Linden, Anthony; Heinemann, Frank W.; Brachvogel, René-Chris; von Delius, Max; Dorta, Romano (Synthesis, 2016)
The ‘privileged’ P-alkene ligand (S)-2 is synthesized on a > 40 gram scale in 96% yield starting from dibenz[b,f]azepine-PCl2 (1; accessible on > 80 g scale) and (S)-BINOL. Similarly, the P-alkenes (R)-3 and the ‘chiral-at-P’ (SP,SC)-4 are obtained from (R)-Taddol [(R,R)-α,α,α',α'-tetraphenyl-2,2-dimethyl-1,3-dioxolane-4,5-dimethanol] and (S)-α,α-diphenylprolinol, respectively, in multigram quantities and high purity. The crystal structures of (SP,SC)-4, its diastereomer (RP,SC)-4, and of the (R)-SPINOL-derived ligand (R)-5 are reported. A slightly revised synthesis of SPINOL is also disclosed.
Keywords: synthetic methods; ligand synthesis; chiral ligands